Detection of osteochondritis dissecans using convolutional neural networks for computer-aided diagnosis of baseball elbow - Sasaki, Kenta; Fujita, Daisuke; Takatsuji, Kenta; Kotoura, Yoshihiro; Sukenari, Tsuyoshi; Minami, Masataka; Kobayashi, Yusuke; Kida, Yoshikazu; Takahashi, Kenji; Kobashi, Syoji (Proceedings / International Symposium on Multiple-Valued Logic, 2023)
Baseball elbow is a kinetic disorder of the elbow caused by repetitive pitching in baseball. Osteochondritis dissecans (OCD), one of the most common forms of baseball elbow, is a disorder of the humeral capitellum of the elbow, and early detection of OCD is important. This study aims to create a model to detect OCD from ultrasound images of the elbow. The model is based on VGG16. The proposed method was validated by using 67 OCD subjects and 91 normal subjects. The results showed that the model achieved an accuracy of 88.5%, a precision of 87.9%, a recall of 97.0%, an F1 score of 0.910, and an AUC of 0.971.